A Proposed Rehabilitation Program for Connective Thigh Muscle Injuries of First Class Football Club Players in Basra Governorate - Ati, Mokhles Makki; Manshid, Mohammed Jaafar Yasir (International Journal of Psychosocial Rehabilitation, 2020)
The research is summarized in the design of the proposed rehabilitation program for people with connective muscle tears for first-class football clubs in Basrah clubs the importance of knowing the effect of the program and its vocabulary on injury, so the researcher used the experimental approach with the system of control and experimental groups with two measurements before and after a sample of twelve (12) injured six (6) Players of them represent the experimental group and the other six (6) players represent the control group, and the results of the research were that there were no statistically significant differences between the pre and post measurements of the control group that used traditional treatment, while it confirmed the existence of statistically significant differences between the two pre-measurements of the experimental group to restore muscle efficiency Macrophages in favor of telemetry.